THE INFLUENCE OF LOCATION, BRAND IMAGE AND PRODUCT QUALITY ON PURCHASING DECISIONS AT PT. SATYALOKA TIRTA AMERTA IN BANGLI DISTRICT - Dewi, Gusti Ayu Utami Sri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
Gaining insights into consumer behavior remains an essential endeavor for companies aiming to cater effectively to their target market, particularly concerning the realm of consumer purchase choices. The objective of this study revolves around exploring the individual and collective impact of geographical location, brand perception, and product excellence on consumer purchase decisions pertaining to the Sangsang brand of bottled mineral water, offered by PT. Satyaloka Tirta Amerta. The scope of the study encompasses all consumers who have engaged in the purchase of Sangsang bottled water within the Bangli Regency, an entity with a population size yet to be determined. To attain a representative sample, the study employs a purposive random sampling method, yielding a sample size of 96 participants as derived from the formula advocated by Rao Purba. The methodology adopted encompasses various analytical techniques, including assessments of classical assumptions, multiple linear regression analyses, determination analyses, F-tests, and t-tests. The culmination of these analyses underscores the pronounced influence of geographical location, brand image, and product quality on consumers' purchasing inclinations. Individually, each factor displays a positive and noteworthy impact, signifying that a suitable location, favorable brand perception, and superior product quality significantly contribute to consumer decisions. When appraised collectively, these three variables sustain their significance, emphasizing their joint effect on consumers' decisions to purchase Sangsang branded bottled water from PT. Satyaloka Tirta Amerta within the Bangli Regency.